2014
DOI: 10.12657/denbio.072.010
|View full text |Cite
|
Sign up to set email alerts
|

Geographical differentiation of Dryas octopetala in Europe based on morphological features

Abstract: Abstract:Dryas octopetala is an important arctic alpine species, but its morphological analyses are scarce. The study deals with present European biogeographical structure based on morphology and its relations to the phylogenetic structure and the climate. Characters of leaves from 23 isolated populations were measured, statistically characterized and analyzed with the use of ANOVA and the discriminant analysis. All the features differentiated the tested samples significantly. Differences between plants repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…1B) and a further 7 resulting from calculations (Table 2). The leaf characteristics were chosen based on previous studies on the variation of S. herbacea L., S. reticulata L. and Dryas octopetala L. (Marcysiak, 2012a(Marcysiak, , 2012b(Marcysiak, , 2014 and from diagnoses of S. retusa group taxa (Pawłowski, 1956;Rechinger, 1957Rechinger, , 1974Dostál, 1989;Koblížek, 2006). The measurement procedure follows those described by Jasińska et al (2015) with implementation of WinFolia Pro 2003 (Regent Instruments Inc.) software.…”
Section: Plant Materials Collection and Measurement Proceduresmentioning
confidence: 99%
“…1B) and a further 7 resulting from calculations (Table 2). The leaf characteristics were chosen based on previous studies on the variation of S. herbacea L., S. reticulata L. and Dryas octopetala L. (Marcysiak, 2012a(Marcysiak, , 2012b(Marcysiak, , 2014 and from diagnoses of S. retusa group taxa (Pawłowski, 1956;Rechinger, 1957Rechinger, , 1974Dostál, 1989;Koblížek, 2006). The measurement procedure follows those described by Jasińska et al (2015) with implementation of WinFolia Pro 2003 (Regent Instruments Inc.) software.…”
Section: Plant Materials Collection and Measurement Proceduresmentioning
confidence: 99%
“…climatic, soil/geological) or natural selection and a potentially different post-glacial history might have shaped this morphological differentiation. Dryas octopetala exclusively occurs in sites with limestone, the Greek populations being no exception (Strid 1986;Schuler & Tsiripidis 2009;Marcysiak 2014). On-site examination showed that D. octopetala occurs in Greece above 1900 m in rocky micro-sites of northern or northwestern exposure (see Appendix), where competition with other plant groups (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf morphology is widely considered as a group of trait variables from which biogeographical information and species evolution can be deduced (Klingenberg 2010;Dkhar & Pareek 2014;Marcysiak 2014;Tian & al. 2016;Lai & al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations